Pengembangan Karir Manajerial dalam Menghadapi Abad 21 - Lindawati, Tuty (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2003)
Career is a job or position which is taken or hold by a person in his work life. For many people, that job is a part of precise constituted planning. If a company wants to survive in this turbulance changing environment, its human resources have to be improved. A paradigm shift in managing an organization will influence the next career management to face 21st century.